A phase-I, open label clinical trial to assess the safety of Tdap vaccine manufactured by Serum Institute of India Pvt. Ltd. in adults. Issue 6 (5th February 2021) - Sharma, Hitt; Anil, K.; Parekh, Sameer; Pujari, Pramod; Shewale, Sunil; Madhusudhan, R.L.; Patel, Jaya; Eswaraiah, Anand; Shaligram, Umesh; Gairola, Sunil; Rao, Harish
Abstract: Background: This first in human study was designed as an open label clinical trial to assess the safety and tolerability of Serum Institute of India Pvt. Ltd. (SIIPL) Tdap vaccine in healthy adult volunteers, aged 18–45 years. Methods: A total of 24 healthy adults were administered a 0.5 ml single dose of SIIPL Tdap vaccine intramuscularly, and were followed for one month for safety outcomes viz., immediate, solicited, unsolicited and serious adverse events. Results: 23 subjects completed the study in compliance with the study protocol. None of the participants experienced any immediate adverse events or any local or systemic solicited adverse events. Conclusion: Tdap vaccine manufactured by Serum Institute of India Pvt. Ltd. is safe and well tolerable in adults. It was concluded that further clinical development of this vaccine should continue to assess its safety and immunogenicity, in the target population. Clinical Trial Registration – CTRI/2017/03/008003.